STUDI TENTANG PENGENALAN DAN PENGGUNAAN BAHASA ARAB - Fatwa Nurhidayati (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2026)
his study examines the introduction and use of the Arabic language among seventh-grade students of State Islamic Junior High School (MTsN) 2 Bandung through the Alef Success digital learning platform. The integration of platform-based educational technology in Arabic language instruction at madrasah institutions has become an increasingly relevant issue amid the digital transformation of Islamic education in Indonesia. This study employs a descriptive quantitative approach using a survey method. The study population comprised all seventh-grade students of MTsN 2 Bandung, with the sample determined through a proportionate stratified random sampling technique. Data collection instruments consisted of a structured Likert-scale questionnaire that had been tested for validity and reliability, supplemented by a basic Arabic language proficiency test. Measurement indicators encompassed the level of vocabulary recognition (mufradat), reading ability (qira'ah), grammatical comprehension (nahwu-sharaf), platform usage motivation, as well as the frequency and intensity of Alef Success utilization in Arabic language learning. Data were analyzed using descriptive statistics including mean scores, percentages, standard deviations, and proficiency level categorization. The results indicate that the level of Arabic language introduction and usage among seventh-grade students through the Alef Success platform falls within the moderately developing category, with a mean score of 64.7 out of a scale of 100. The highest indicator was found in the aspect of basic vocabulary recognition, while the lowest indicator was observed in the aspect of grammatical mastery. This study recommends the optimized and integrated use of the Alef Success platform in conjunction with pedagogical approaches employed by Arabic language teachers at madrasah institutions, with the aim of enhancing students' linguistic competence in a comprehensive and sustainable manner.